Application of Satellite Remote Sensing to find Soil Fertilization by using Soil Colour: study area Vellore District, Tamil Nadu, India. - Suresh Kumar, N; Anouncia, S. Margret; Prabu, M. (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Nowadays the usage of Remote Sensing and GIS techniques are too vast and many Earth observations had been done by Remote Sensing and GIS techniques. The innovation of this work is to use the LANDSAT image data and GIS Techniques to assess land information and soil classification in the most coming up area of Vellore district and propose the possible fertilization for this study area. Landsat image is classified by minimum distance classification algorithm and according to the reflectance characteristics of the surface material. From the classified data we can find out the best fertilization for the best soil using colour of the soil. It is proved that, within limitations the classification algorithms and threshold parameters have an important influence on the classification result